Bone Regeneration of a 3D-Printed Alloplastic and Particulate Xenogenic Graft with rhBMP-2 - Ji-In Ryu (MDPI AG, 2021)
This study aimed to evaluate the bone regeneration capacity of a customized alloplastic material and xenograft with recombinant human bone morphogenetic protein-2 (rhBMP-2). We prepared hydroxyapatite (HA)/tricalcium phosphate (TCP) pure ceramic bone blocks made using a 3D printing system and added rhBMP-2 to both materials. In eight beagle dogs, a total of 32 defects were created on the lower jaws. The defective sites of the negative control group were left untreated (N group; 8 defects), and those in the positive control group were filled with particle-type Bio-Oss (P group; 12 defects). The defect sites in the experimental group were filled with 3D-printed synthetic bone blocks (3D group; 12 defects). Radiographic and histological evaluations were performed after healing periods of 6 and 12 weeks and showed no significant difference in new bone formation and total bone between the P and 3D groups. The 3D-printed custom HA/TCP graft with rhBMP-2 showed bone regeneration effects similar to that of particulate Bio-Oss with rhBMP-2. Through further study and development, the application of 3D-printed customized alloplastic grafts will be extended to various fields of bone regeneration.